Classification of Intervertebral Disc Disease - Fenn, Joe; Olby, Natasha J.; , The Canine Spinal Cord Injury Consortium (CANSORT-SCI); Moore, Sarah A.; Olby, Natasha J.; Gjessing, Kady M.; Davidson, Rhanna M.; Levine, Jonathan M.; McWhorter, Helen; Lewis, Melissa J.; Jeffery, Nick D.; Mullins, Maureen E.; et al. (Frontiers in Veterinary Science, 2020)
Intervertebral disc disease (IVDD) has been recognised in dogs since the 1800s, when the first descriptions of extruded disc material within the vertebral canal were published. In the intervening time our understanding of intervertebral disc pathology in dogs and cats has increased dramatically, with many variations of IVDD described. Whilst the volume of literature and collective understanding of IVDD has expanded, there has also been scope for confusion as the definition of intervertebral disc disease, with its myriad different manifestations, becomes more complicated. A large volume of literature has aimed to combine the use of histopathology, diagnostic imaging and clinical findings to better understand the various ways in which IVDD can be classified. Much of this research has focused on the classification of mechanisms of intervertebral disc degeneration, centering around the differences between, and overlaps in, IVDD in chondrodystrophic and non-chondrodystrophic dog breeds. However, with the increasing availability of advanced imaging modalities allowing more accurate antemortem diagnosis, the concept of IVDD has expanded to include other clinical presentations that may not fit into traditional models of classification of IVDD. This review aims to provide an up to date overview of both historical and current systems of IVDD classification, highlighting the important findings and controversies underpinning them.